Does God Create Evil? A Study of Fakhr al-Dīn al-Rāzī’s Exegesis of Sūrat al-falaq - Faruque, Muhammad U. (Islam and Christian-Muslim relations, 2017)
The present piece of research analyses Fakhr al-Dīn al-Rāzī’s exegesis of Sūrat al-falaq in his voluminous tafsīr, Mafātīḥ al-ghayb. In his exegesis of Sūrat al-falaq, al-Rāzī draws on the insights of philosophical Sufism (ʿirfān), philosophy, and science in general, in addition to the transmitted (naqlī) sciences. The focus of al-Rāzī’s exegesis in this chapter is the problem of evil. According to al-Rāzī, evil is found only in the sublunar world, that is, the world of generation and corruption. And this is so owing to the fact that the sublunar world contains bodily substances, in contrast to the world of spirit, in which only spirits (arwāḥ) dwell. However, as his exegesis segues into the specific verses of Sūrat al-falaq, it begins to take a more polemical turn against the Muʿtazilites and other theological opponents. Al-Rāzī’s theodicy remains faithful in part to his Ashʿarite predecessors and, although he attempts to deconstruct the Muʿtāzilite position on this issue, he does not present an alternative doctrine in his tafsīr. Instead, his response (after refuting his opponents) betrays a combination of scriptural evidence and rational arguments that seek to valorize divine omnipotence.